PENGARUH KESEPIAN, MOTIF PERSAHABATAN, KOMUNIKASI ON LINE DAN TERHADAP PENGGUNAAN INTERNET KOMPULSIF PADA REMAJA - Dariyo, Agus (Jurnal Psikologi : Media Ilmiah Psikologi, 2013)
AbstractLoneliness as a feeling of emotion which someone feel alone withaout the other people in her / his life. Actually, someone need the presence of the other people in her / his life, because human is social creature of God. Therefore, someone has friendship motive. The friendship motive will make someone to seek a friend to build the social community. One of ways for seeking a friend is use the on line communication. By using internet, someone can make a network to connect to the other people in the world. But if someone has no the self-regulation in her / his life, he/she will improve the internet addiction. Internnet addiction is a bad habit to use internet without stoping. This research want to explain the effect of loneliness, friendship motive, on line communication on the internet addition of adolescence. This research use the 4 quostioneries consist of loneliness, friendship motive, on line communication, and the internet addiction quostioner, By using multiple regression analisys (N = 286), result of the research are the significant effect of lonelines, friendship motive, on line commnication on the internet addiction of adolescence (13,2 %). And there are the other factor which effect on the internet addiction on adolescence (86,8 %). But partially, there is only on line communication which effect on the internet addiction. Actually, loneliness and friendship motive have no effect on the internet addiction ( t=6,324, p 0,000<0,05)Keywords: loneliness, friendship motive